Sexual dimorphism in the sonic system and otolith morphology of Neobythites gilli (Ophidiiformes). (22nd April 2018) - Parmentier, E.; Boistel, R.; Bahri, M. A.; Plenevaux, A.; Schwarzhans, W.
Abstract: Although males and females of many sound‐producing fish species may show differences at the level of the sonic apparatus, otoliths are usually species specific having intraspecific variation only if exposed to different environmental condition or in relation with the fish size. This study reports sexual dimorphism at the level of both otolith shape and sonic apparatus in the ophidiid Neobythites gilli . As it is the case in other Neobythites species, sound‐producing apparatus is better developed in males. Due to their way of life in darker or deep waters, differences at the level of the sound‐producing apparatus support more constraints related to acoustic communication for sex recognition or mate localization. Otolith modifications concern only Neobythites male specimens, whereas otolith of females are virtually unchanged when compared to sister species without sexual dimorphism, meaning this feature would not be related to sexually induced differences in calling. Differences between the otoliths of males and females could therefore be related to their way of life. Abstract : Sexual dimorphism of the acoustic apparatus in Neobythities gilli show males are better callers. Unusual sexual dimorphism of the sagitta (otoliths) in Neobythities gilli . Sexual dimorphism in the hearing apparatus seems related to the way of life and not to hearing abilities.